EFFECT OF FOLIAR SPRAY WITH SEAWEEDS EXTRACT ON GROWTH , YIELD AND SEED VIGOUR OF BREAD WHEAT CULTIVARS - H. Saudi, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Two factorial experiments were conducted .The first one was field experimental which was carried out at the one of  agricultural farms in Thi-Qar governorate – Nassiriyah district during the winter seasons of 2014 - 2015 and 2015 - 2016  .The second was carried out in the laboratories of Agriculture and Marshes Colle. , Univ. of Thi-Qar  . The aim was to investigate the effect of foliar application of seaweed extract on growth , yield and seeds vigour of four bread wheat cultivars . The design of field experiment was (RCBD) in factorial experiments with three replications in two factors .The first factor included four wheat cultivars ( Bohooth -22, Al-tahadi , IPA – 99 and Al-Rasheed ) . The second factor included foliar application by two seaweed extract concentrations (2 and 4) ml L-1 in addition to control treatment (without seeweed extract) . The design of Lab. experiment was (RCD) in factorial experiments with four replications in two factors. The results of field experiment showed that IPA – 99 cultivar gave highest averages of flag leaf area (42.17 and 44.81) cm2 , tillers number (435.42 and 443.61) tillers m-2, spikes number (387.05 and 392.33) spike m-2 , 1000 grain weight (38.75 and 40.56) gm and grain yield (4.67 and 4.75) tan ha-1 in both season, respectively . Wheat plants that sprayed with seaweed extract concentration 4 ml.L-1 gave highest averages of flag leaf area (40.25 and 43.34) cm2 , spikes number (384.07 and 387.91) spike m-2 , 1000 grain weight (38.32 and 39.78) gm and grain yield (4.50 and 4.64) tan ha-1 in both season, respectively. The plants of IPA – 99 cultivar which sprayed  with seaweed extract concentration 4 ml L-1 gave highest averages of flag leaf area (44.25 and 47.12) cm2 , spikes number (393.32 and 398.95) spike m-2 , 1000 grain weight (40.11 and 42.98) gm and grain yield (4.91 and 4.97) tan ha-1 in both season, respectively. The results of  Lab. experiment showed that the seeds produced from IPA – 99 cultivar gave highest germination speed index (28.85 and 30.60) ,  standard germination percentage (92.56 and 93.19)% and lower mean of germination time mean ( 5.26 and 4.99 ) day in both season, respectively. The seeds produced from wheat plants that sprayed with seaweed extract concentration 4 ml L-1 gave highest averages of germination speed index (30.04 and 31.66) ,  standard germination percentage (93.18 and 93.53)% and lower mean of germination time mean ( 5.15 and 4.87 ) day in both season, respectively . It can be conclude the superiority of the plants of IPA – 99 cultivar which sprayed with seaweed extract concentration 4 ml L-1 .